2000
DOI: 10.1042/bj3500353
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the kinetic properties of the lipid- and protein-kinase activities of the p110α and p110β catalytic subunits of class-Ia phosphoinositide 3-kinases

Abstract: Growth factors regulate a wide range of cellular processes via activation of the class-Ia phosphoinositide 3-kinases (PI 3-kinases). We directly compared kinetic properties of lipid- and protein-kinase activities of the widely expressed p110alpha and p110beta isoforms. The lipid-kinase activity did not display Michaelis-Menten kinetics but modelling the kinetic data demonstrated that p110alpha has a higher V(max) and a 25-fold higher K(m) for PtdIns than p110beta. A similar situation occurs with PtdIns(4,5)P(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 43 publications
6
28
1
Order By: Relevance
“…In contrast to the predominant autophosphorylation of p110␤ observed in this and previous studies (27), others have reported p85 phosphorylation as the major target of PI3K␤ autophosphorylation (25,26). In order to explain the apparent discrepancies, one must consider the experimental conditions used in these studies.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In contrast to the predominant autophosphorylation of p110␤ observed in this and previous studies (27), others have reported p85 phosphorylation as the major target of PI3K␤ autophosphorylation (25,26). In order to explain the apparent discrepancies, one must consider the experimental conditions used in these studies.…”
Section: Discussioncontrasting
confidence: 71%
“…Recent reports have described autophosphorylation of both subunits of PI3K␤ (i.e. p85 and p110␤) (25)(26)(27). In order to analyze autophosphorylation of PI3K isoforms in vitro, we expressed recombinant heterodimeric PI3K␣ and PI3K␤ in insect cells and measured their protein kinase activities (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another estimate for the same concentration was 6.7 M from the calculated PtdIns(4,5)P 3 concentration from the measurement of 1.8 ng PtdIns(4,5)P 2 per 10 6 neutrophils (65), while taking into account the volume of a single neutrophil, which is on the order of 270 m 3 (66). These estimates are consistent with the relationship ͓S͔ Ͻ Ͻ K m from Equation 4, and the value of the Michaelis-Menten constant for PI3K on the order of K m ϭ 100 M (54). The total enzyme concentration, 30 nM PI3K, was calculated from the total number of available binding sites for wortmannin per neutrophil, which is on the order of 5,000 molecules (58).…”
Section: Reducing Enzyme Activitysupporting
confidence: 59%
“…The relative enzymatic activity of p110␣ is higher than that of other isoforms (49,50), suggesting that the inability of the wild type p110␣ to induce transformation is not due to low specific activity. Western analyses suggest that the non-␣ isoforms of p110 are expressed at higher levels than p110␣, assuming that the sensitivities of isoform detection by the different antibodies are roughly comparable (Fig.…”
Section: Discussionmentioning
confidence: 96%